A review of the Villafranchian fossiliferous sites of Latium in the framework of the geodynamic setting and paleogeographic evolution of the Tyrrhenian Sea margin of central Italy. (1st July 2018) - Marra, F.; Petronio, C.; Salari, L.; Florindo, F.; Giaccio, B.; Sottili, G.
Abstract: In the present study we provide a paleontological and chronostratigraphic review of the Villafranchian fossiliferous sites of Latium, revising the biochronologic attribution based on their framing within the geodynamic and paleogeographic evolutionary picture for this region. Aimed at this scope, we reconstruct the sedimentary and structural history of the Early Pleistocene marine basins through the review and the regional correlation of published stratigraphic sections and borehole data. Moreover, we combine the chronostratigraphic constraints provided in this study to the near-coast deposits of Gelasian-Santernian age (2.58–1.5 Ma) with the results of a recent geomorphologic study of this area, allowing us to reconstruct a suite of terraced paleo-surfaces correlated with marine isotopic stages 21 through 5. By doing so, we provide further age constraints to the sedimentary and tectonic processes acting on the Tyrrhenian Sea margin in Quaternary times, highlighting a possible different paleogeographic evolution of the southern coastal area where the Middle-Villafranchian type-section of Coste San Giacomo site is located, with respect to the northern sector. Highlights: We provide a paleontological and chronostratigraphic review of the Villafranchian sites of Latium. We reconstruct the paleogeographic evolution of the Plio-Pleistocene marine basins of the central Tyrrhenian Sea. We provide an overview of the structural and stratigraphic setting of the Tyrrhenian Sea margin. We provide chronologic boundaries to the Middle-Pleistocene volcano-tectonic processes.